The issue of funding higher education: Global patterns compared to South African case: - Wolhuter, C. C. (South African Journal of Higher Education, 2023)
In the past 30 years, since c. 1990, a higher education revolution has taken place in all parts of the world. This has been a costly exercise, and while the global higher education revolution can boast an enrolment explosion and has opened the doors of higher education to many, it has taken place within the parameters of the neoliberal economics, meaning that the imperatives of social justice and equity have not been adequately responded to. The pivot between this contextual force of neoliberal economics and the contextual imperative for social justice in higher education is funding. South Africa is part of this global revolution, although the specific contextual ecology of the country too has had an impact on the form this revolution has been taking on. In this article, the issue of higher education funding in South Africa is investigated from the theoretical framework and with the methodological apparatus of comparative and international education. This framework and methodological apparatus are explained. Then the main tenets and context of the worldwide higher education revolution vis-à-vis the imperatives of social justice and equity are reconstructed, and the South African case is interpreted and assessed against this global canvas in order to suggest a forward trajectory for South African higher education.